Pengaruh Jumlah Unit Usaha, Investasi Dan Output UMKM Terhadap Kemiskinan - Sri Oktavani; Yulhendri Yulhendri (Universitas Negeri Padang, 2021)
This study aims to analyzed the effect of the number of business units, investment and output of MSMEs on poverty in West Sumatra. The object of this research is the Regency / City in West Sumatra Province. This study uses the Least Square Panel method to see the effect of independent variables on the dependent variable as seen from the Regency / City of West Sumatra Province from 2014 to 2017 which was collected through documentation from related government agencies. This study uses a Random Effect Model (REM) approach. The results of this study indicate that (1) the number of business units, investment and output of MSMEs does not have a significant effect together on poverty in West Sumatra Province. (2) The number of business units does not have a significant effect on poverty in West Sumatra. (3) Investment does not have a significant effect on poverty in West Sumatra. (4) UMKM output has a significant effect on poverty in West Sumatra. From the results of the study, it is suggested that all subjects pay more attention to these factors to alleviate poverty and improve community welfare, be aware of the akak of poverty.Keywords : business unit, investment, umkm output, poverty